Assessing Fisher’s Perception on Disaster Management Across Coastal Kerala - Shyam S. Salim; Aswathy N.; Harsha Elizabeth James (Journal of Indian Fisheries Association, 2018)
In the wake of cyclone Ockhi that struck Kanyakumari district in Tamil Nadu and parts of Kerala on November 29th, 2017, disaster management has again caught the attention of fishermen and policymakers. Disaster Management in fisheries essentially deals with management of resources and information as far as a disastrous event is concerned and also how effectively and seamlessly one coordinates these resources.Data related to the perception of fishermen regarding current disaster management in place and the information services provided were collected from the stakeholders’ representing fishermen across the state of Kerala and was analysed using statistical tools such as percentage analysis and Garrett ranking for deriving conclusions out of the survey data. Among the 52 per cent of the respondents who reported to have encountered huge losses due to natural disasters, 53 per cent encountered at least one disaster in the last decade followed by 28 per cent encountering at least two. Sixty-seven per cent respondents estimated that the average loss per household would be in the range of Rs.50000-100000. The respondents (55 %) opined that they are not satisfied with the support / welfare measures provided by the government and mentioned the delay in disbursement of funds and its diversion, mentioned the delay in disbursement of funds and its diversion, delay in sea wall construction as the main constraints. Only 16%, 14% and 12 % of the respondents received information related to ’Tsunami Alert system, Ocean sate forecast and cyclone & PFZ, respectively. The respondents mentioned information not reaching fishers, complexity or difficulty in understanding she information provided, language issues, delay in receipt and insufficient information as the main constraints faced by fishermen in relation to information dissemination. Error free and accurate weather forecasting, digital display across major landing centers for information dissemination, engaging ISG in information sharing, providing gadgets with governmental support and efficient usage of mobile for information sharing are the main suggestions put forward by the respondents Tor ensuring better disaster management.